Point-of-care haemoglobin testing in African hospitals: a neglected essential diagnostic test - Uyoga, Sophie (Br J Haematol, 2021)
Owing to the rapid turnaround time in the assessment of haemoglobin level by point-of-care tests (POC Hb), these have grown in popularity and scope in large parts of the world. However, whilst POC testing for malaria and HIV remains has been integrated into patient management in Africa, the use of POC haemoglobin testing remains neglected by health services. The main users of transfusions (paediatric, maternity and trauma services) present largely as emergencies. Ward-based POC Hb could result in more rapid and accurate diagnosis of anaemia, contributing to saving of lives and at the same time reduce unnecessary transfusions which deplete the limited supplies of donated blood in Africa. Severe anaemia requiring transfusion is a major cause of paediatric admission in Africa. At a dissemination meeting to discuss the results of a large phase III paediatric transfusion trial and steps to implementation of the findings participants strongly recommended that one of the most pressing actions required was to prioritise the use of POC haemoglobin testing. This would facilitate implementation of the new transfusion algorithm, developed at the meeting, which refines patient management including blood transfusions. We present the rationale for the strongly recommended prioritisation of POC Hb, using paediatric transfusion as an exemplar.